Transformation of earthquake disaster victims' shelter into sustainable home: the case of Lar City, Iran - Dola, Kamariah; Parva, MMohammad (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Earthquake damages are immeasurable. To cope with losses, especially when it involves thousands of victims is not easy. Often, the survivors need immediate shelter and counselling especially when the lost involved homes and their love ones. This paper discusses transformation of temporary shelters for earthquake victims into a more sustainable home, using the case of Lar city in Iran. The paper cantered on the issue of mismatch of the design of the shelter with occupants’ socio-cultural needs that resulted dissatisfaction among occupants leading to various transformation designs and chaotic facades. The study documents transformation of 365 immediate shelters into what the owners finally called homes over a period of more than 40 years. Methodology involves document analysis of maps and records during the occupancy period, observation, questionnaire survey and interviews. This paper concludes that majority of transformations were into traditional architectural design. This paper suggests that to improve residents’ satisfaction for future development for housing for disaster victims, consideration of socio-culture of local and user needs should be given priority to avoid dissatisfaction and further house transformation cost